Conservation of 'carola' roses using substances with biocide potential - Bastos F.E.A.* (2016)
Two experiments were conducted to evaluate the effect of different preservative solutions on maintaining postharvest quality of red roses cultivar 'Carola'. The treatments evaluated in both experiments were five preservative solutions: (S) sucrose (1%) (SAC) sucrose (1%) + citric acid (0.2 g L-1), (SACH) sucrose (1 %) + citric acid (0.2 g L-1) + sodium hypochlorite (1%) (SACA) sucrose (1%) + citric acid (0.2 g L-1) + rosemary oil (Rosmarinus officinalis L.) (100 uL L-1), (SACG) sucrose (1%) + citric acid (0.2 g L-1) + Oil Ginger (Zingiber officinale) (100 uL L-1). In the first experiment the rods were maintained for 10 days in refrigerator at 3 ± 1 °C and in the second experiment were maintained for five days in refrigerator (3 ± 1 °C) and five days at ambient conditions (19 ± 1 °C). The variables evaluated were swelling, curvature of the floral stalk, browning petals, floral opening and colored petals, in both experiments, and coloring of the petals in the second experiment. The evaluations were performed every two days during the storage period in experiment 1, and daily during the shelf period in experiment 2. The experimental design in both experiments was a randomized complete block design with four replications and two branches each. In the first experiment, the use of sucrose was shown to be as effective as the other preservative solutions, preserving the roses up to 10 days in cold storage at 3 ± 1° C. In the second experiment, for the solution containing sucrose alone, the use of sodium hypochlorite, rosemary oil, and ginger oil showed the best results in maintaining the quality of the rods, and essential oils gave better preservation of roses.